Air monitoring with passive samplers for dioxin-like persistent organic pollutants in developing countries (2017–2019). (January 2022) - Abad, Esteban; Abalos, Manuela; Fiedler, Heidelore
Abstract: As part of the global monitoring plan on persistent organic pollutants (GMP) under the Stockholm Convention passive air samplers equipped with polyurethane foam disks (PUFs) were applied to monitor dioxin-like POPs. For sampling, toluene-pretreated PUFs were exposed for three months during two years. Chemical analysis was performed in one accredited expert laboratory using internationally accepted methods; for comparison, all results were normalized to one PUF and 3 month exposure. Total TEQs, using WHO2005 -TEFs, were lowest in the Pacific Islands countries (PAC) and had similar mean values in Africa (16.8 pg TEQ/PUF), Asia (16.9 pg TEQ/PUF), and Latin American and Caribbean countries (GRULAC, 13.3 pg TEQ/PUF). Using median values, Asia (13.4 pg TEQ/PUF) and GRULAC (13.1 pg TEQ/PUF) had higher amounts than Africa (6.1 pg TEQ/PUF) and PAC (2.1 pg TEQ/PUF). The contribution of PCDD/PCDF to the total TEQ was 2-3-times higher than from the dl-PCB. Mono-ortho PCB did not play a role in any of the samples. The previous 40 samples during 2010/2011 and the present 195 samples from 2017/2018 did not show a statistical difference (p value = 0.3), only for GRULAC, a downward trend was identified. It is recommended combining 4 PUFs to 'annual' samples. Graphical abstract: Image 1 Highlights: Highly standardized protocol for sampling, chemical analysis and assessment. One PUF and 3 months often not sufficient to quantify dl-POPs; longer periods recommended. Downward trend for PCDD/PCDF and dl-PCB (as TEQ) only confirmed in Latin American region. Maximum values for PCDD/PCDF and dl-PCB (as TEQ) were found in Africa.